Book review - Adding some TEC-VARIETY: 100+ activities for motivating and retaining learners online - Maggie Hartnett (Flexible Learning Association of New Zealand, 2014)
With the increasing ubiquity of online and blended learning, more and more educators are being asked to teach online, often without any specific specialist training. Adding some TEC-VARIETY: 100+ activities for motivating and retaining learners online by Bonk and Khoo is a practical 'how to' guide for motivating learners in online and blended learning contexts. Drawing from a rich base of research into motivation, this book provides a framework and an extensive set of associated online instructional activities that anyone involved in teaching online, from primary through to tertiary education, can use to engage and motivate learners.